Altitudinal Patterns in Adaptive Evolution of Genome Size and Inter-Genome Hybridization Between Three Elymus Species From the Qinghai–Tibetan Plateau - Chen, Zhao; Guan, Yongzhuo; Han, Mengli; Guo, Yuxia; Zhang, Jingxue; Guo, Zhipeng; Sun, Genlou; Yan, Xuebing (Frontiers in Ecology and Evolution, 2022)
Genome size variation and hybridization occur frequently within or between plant species under diverse environmental conditions, enriching species diversification and promoting powerful driving forces on the evolutionary process. Elymus L. is the largest genus in Triticeae with five recognized genome donors (St, H, P, W and Y). However the data validation for population cell genetics of Elymus species are sparse, especially whether genome hybridization and chromosomal data can be affected by altitude are still unknown. In order to explore the relationship among genome size, interspecific hybridization and altitude of Elymus species at population genetic and cytological levels. 27 populations at nine different altitudes (2800-4300 m) of three Elymus species, hexaploid E. nutans (StHY, 2n=6x=42), tetraploid E. burchan-buddae (StY, 2n=4x=28) and E. sibiricus (StH, 2n=4x=28), were sampled from the Qinghai-Tibetan Plateau (QTP) to estimate whether intraspecific variation could affect the genomic relationships by genomic in situ hybridization (GISH) and measure the differences in the genome size of Elymus among different altitude ecological groups by flow cytometry. The genome size of E. nutans, E. burchan-buddae and E. sibiricus varied from 12.38-22.33, 8.81-18.93, and 11.46-20.96 pg/2C with the averages of 19.59, 12.39, and 16.85 pg/2C separately. And a strong correlation between altitude and nuclear DNA content was observed in three Elymus species by the curve regression analysis. Additionally, the chromosomes of the St and Y genomes demonstrated higher polymorphism than those of the H genome. Larger genome size variations occurred in the mid-altitude regions (3900-4300 m) compared to other-altitudes populations. This research suggests notable altitudinal pattern in genome size variation and interspecific genome hybridization of wild wheatgrass, facilitating to account for genome evolution shaped by altitude, supporting our former hypothesis of genetic richness center at medium altitude which will be useful and valuable for species adaptation to highland environmental conditions, germplasm utilization and conservation.